From MTA to New Biomaterials Based on Calcium Silicate - Tanomaru DDS, MSD, PhD, Mario; Viapiana DDS, MSD, PhD, Raqueli; Guerreiro DDS, MSD, PhD, Juliane (Odovtos - International Journal of Dental Sciences, 2016)
One of the most revolutionary materials introduced in Endodontics was the Mineral Trioxide Aggregate (MTA). The investigations regarding MTA formulation allowed researchers to disclose the composition and also some clinical problems related to the clinical application of this material. The augmentation on MTA’s studies resulted in the development a new generation of Endodontic materials, the calcium silicate-based cements. Thus, a brief description of new cements and the perspectives on calcium silicate-based materials development were presented in this communication.